2018
DOI: 10.3389/fpubh.2018.00262
|View full text |Cite
|
Sign up to set email alerts
|

The Health of Arab Americans in the United States: An Updated Comprehensive Literature Review

Abstract: Background: Arab Americans are a historically understudied minority group in the United States and their health needs and risks have been poorly documented. We aim to provide an updated comprehensive review of the literature on Arab American physical and mental health and provide suggestions for future work in this field.Methods: A comprehensive review of the English language medical and public health literature published prior to 2017 identified through multiple database searches was conducted with search ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
128
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 235 publications
7
128
0
Order By: Relevance
“…For example, it has been reported that they are usually not provided with sufficient information regarding appropriate medication use [28]. Furthermore, few disease self-management interventions have been tailored to enable their application to be adapted to ethnic minority patients [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that they are usually not provided with sufficient information regarding appropriate medication use [28]. Furthermore, few disease self-management interventions have been tailored to enable their application to be adapted to ethnic minority patients [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Arab immigrants arrived in several waves from 22 Arabic‐speaking countries in southwestern Asia and North Africa (Samhan, 2001). For a variety of reasons (e.g., religious minority, media stigmatization, lack of clear racial identifier), Arab American adolescents are often victims of discrimination, stereotyping, and prejudice (Abuelezam, El‐Sayed, & Galea, 2018; Ahmed, Kia‐Keating, & Tsai, 2011; Goforth, Oka, Leong, & Denis, 2014). Yet, recent literature reviews revealed that Arab Americans are understudied in health research (Abuelezam et al, 2018; El‐Sayed & Galea, 2009; Rousseau, Jamil, Bhui, & Boudjarane, 2015).…”
mentioning
confidence: 99%
“…For a variety of reasons (e.g., religious minority, media stigmatization, lack of clear racial identifier), Arab American adolescents are often victims of discrimination, stereotyping, and prejudice (Abuelezam, El‐Sayed, & Galea, 2018; Ahmed, Kia‐Keating, & Tsai, 2011; Goforth, Oka, Leong, & Denis, 2014). Yet, recent literature reviews revealed that Arab Americans are understudied in health research (Abuelezam et al, 2018; El‐Sayed & Galea, 2009; Rousseau, Jamil, Bhui, & Boudjarane, 2015). Only a small number of studies have been conducted on the effects of bullying victimization among Arab American adolescents (Albdour et al, 2017; Tabbah, Miranda, & Wheaton, 2016), and no studies have been conducted on the health outcomes of these adolescents who are perpetrators of bullying.…”
mentioning
confidence: 99%
“…National organizations such the U.S. Council of Muslim Organizations, American Muslim Health Professionals, and Islamic Medical Association of North America, as well as relevant regional and community organizations should consider developing targeted messaging, and workshops and trainings that assist Islamic centers in PA program development and promotion in general, which in turn could be advertised on websites. Doing so is particularly important in light of our findings and the prevalence of morbidity associated with insufficient PA found among Muslims in the U.S. [ 6 , 7 , 8 , 9 ]. As well, imams, who play a major role in matters related to Muslim community health, should also receive training for how to incorporate PA promotion into day-to-day ministry and chaplaincy activities [ 26 , 27 , 47 ] and ensure that PA programming is sufficiently advertised.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity disparity based on religion also exists: 38 Muslim countries were 1.2 times more likely to be physically inactive than 94 non-Muslim countries, and within the Muslim countries, women’s physical inactivity prevalence (35.5%) was 1.4 times greater than men’s [ 5 ]. Insufficient PA is a risk factor for overweight, diabetes, and cardiovascular disease, and (perhaps) consequently their prevalence is alarmingly and disproportionately high among various ethnic groups of Muslims and Muslim women living in the United States (U.S.) [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%